Visioning future treescapes in upland landscapes: using deliberative processes to understand values and land-use preferences of local stakeholders - Alix Syder; Susan Baker; Euan Bowditch; Sheena Carlisle; Tom Finch; Melissa Minter; Natasha Constant (Ecosystems and People)
UK environmental policy places an increasing emphasis on large-scale land-use change, with tree-planting objectives set to contribute towards meeting legislated climate and environmental targets. Upland landscapes might expect to see disproportionate change because of the perception that opportunity costs (e.g. from foregone agricultural activities) are low. However, without considering the preferences of local stakeholders, delivery may be misaligned, underlying conflicts not considered and local actors alienated. Land-use preferences are shaped by the values stakeholders attribute to landscapes, and broader contextual factors, both biophysical (i.e. climate change) or institutional (i.e. land-use policy and financial instruments). This paper explores the relationship between values, contextual factors, and land-use preferences, by applying Participatory Scenario Planning (PSP) to design future land-use visions of local stakeholders in two upland landscapes in England (North Pennines and Dales) and Wales (Elenydd). The paper address two overarching research questions (1) How do different stakeholders value upland landscapes? and (2) How does context shape stakeholders’ decisions regarding future land-use? Whilst our results show a greater potential for treescape expansion in the uplands than expected, underlying nuances of land-use preferences demonstrate challenges to treescape expansion here. Our approach also highlights the importance of taking into account contextual factors when examining land-use preferences, for example climate change as a positive driver for on-farm treescape measures, whereas regulatory context limit stakeholders’ ambition for change. Only by understanding these complexities through deliberative processes can future treescape expansion at local scales achieve the best outcomes for people and nature.